Biomagnetic Fluid Flow and Heat Transfer Study of Blood with Gold Nanoparticles over a Stretching Sheet in the Presence of Magnetic Dipole - Jahangir Alam; Ghulam Murtaza; Efstratios Tzirtzilakis; Mohammad Ferdows (Fluids, 2021)
In this study, we examined the biomagnetic flow and heat transfer of an incompressible electrically conductive fluid (blood) containing gold nanoparticles over a stretching sheet in the presence of a magnetic dipole. In this problem, both principles of magnetohydrodynamics (MHD) and ferrohydrodynamics (FHD) were adopted. Biot number and slip and suction parameters were taken into consideration. The nonlinear partial differential equations were transformed into ordinary differential equations by implementing similarity transformations. The numerical solution was attained by utilizing the bvp4c function technique in MATLAB R2018b software. The influence of pertinent parameters involved in this model, such as ferromagnetic parameter, magnetic field parameter, Grashof number, Eckert number, suction parameter, Biot number, slip parameter and Prandtl number, on the dimensionless velocity, temperature, skin friction and heat transfer rate were analyzed numerically and are represented graphically. Among the numerous results, it was observed that increment in ferromagnetic parameter and Prandtl number results in decrement of the velocity and temperature, respectively. For some values of the parameters, a comparison with the results of other documents in the literature is also made.